The Influence of Electronic Discharge Planning in Patients with Heart Failure: A Literature Review - Anggi Aryadi; Fitri Arofiati (Universitas Aisyah Pringsewu, 2021)
The application of electronic discharge planning in heart failure patients is considered important because it offers the right treatment to patients by making it easier for patients to record patient complaints from home and then send them electronically for doctors to see and follow up. This review aims to determine the effect of implementing electronic discharge planning in patients with heart failure. Systematic review was reviewed using journal articles of the last five years from 2015-2020 and full text. The 3 databases used are PubMed, Cochrane and Google Scholar using the keywords electronic discharge planning, electronics, mobile, smartphone, application, CHF, HF and heart failure. From a total of 487,676 journal articles that have been identified, 7 journal articles have been submitted. A total of 2 articles state that the application of electronic discharge planning does not affect the patient's quality of life, while 3 other journal articles stated that there was an effect on the patient's quality of life. 2 articles say the implementation of electronic discharge planning has an effect on self-care, 2 other articles show that electronic discharge planning increases knowledge, and 1 other journal article shows that electronic discharge planning has an effect on medication adherence. Electronic discharge planning to facilitate workers health in the monitoring of patients from a distance away, the app is also able to improve the quality of life, care of self, knowledge and adherence to take the drug on patients with heart failure. Penerapan electronic discharge planning pada pasien gagal jantung dinilai penting karena menawarkan penanganan yang tepat kepada pasien dengan memudahkan pasien mencatat keluhan pasien dari rumah kemudian mengirimkannya secara elektronik untuk dilihat dan ditindaklanjuti oleh dokter. Review ini bertujuan untuk mengetahui pengaruh penerapan electronic discharge planning pada pasien gagal jantung. Tinjauan sistematis menggunakan artikel jurnal lima tahun terakhir dari 2015-2020 dan teks lengkap. 3 database yang digunakan adalah PubMed, Cochrane dan Google Scholar menggunakan kata kunci electronic discharge planning, electronics, mobile, smartphone, aplikasi, CHF, HF dan gagal jantung. Dari total 487.676 artikel jurnal yang telah teridentifikasi, 7 artikel jurnal telah diajukan. Sebanyak 2 artikel menyatakan penerapan electronic discharge planning tidak berpengaruh terhadap kualitas hidup pasien, sedangkan 3 artikel jurnal lainnya menyatakan ada pengaruh terhadap kualitas hidup pasien. 2 artikel menyebutkan implementasi electronic discharge planning berpengaruh terhadap perawatan diri, 2 artikel lainnya menunjukkan electronic discharge planning meningkatkan pengetahuan, dan 1 artikel jurnal lainnya menunjukkan electronic discharge planning berpengaruh terhadap kepatuhan minum obat. Electronic discharge planning dapat memudahkan petugas kesehatan dalam memantau pasien dari jarak jauh, aplikasi ini juga mampu meningkatkan kualitas hidup, perawatan diri, pengetahuan dan kepatuhan minum obat pada pasien gagal jantung.